Missed nursing care in the Malaysian context: A cross‐sectional study from nurses' perspective. (27th February 2021) - Nahasaram, Sri Theyshaini; Ramoo, Vimala; Lee, Wan Ling
Abstract: Aim: To determine the occurrence, factors and outcome of missed nursing care from the perspective of Malaysian nurses. Background: Missed nursing care is an important issue in the global health care sector. However, little is known on the extent of missed nursing care in the Malaysian context and its contributing factors. Methods: A cross‐sectional design was adopted for data collection using the MISSCARE Survey instrument. Participants comprised 364 nurses from medical and surgical wards of a large teaching hospital. Data were analysed using descriptive, binomial logistic and hierarchical regression analyses. Results: The overall occurrence of missed nursing care was 1.88 (on a scale of 1.00–5.00), which differed across 24 nursing care elements. Basic nursing care and communication‐related care were the most frequently missed elements. Types of ward and labour resources were identified as contributing factors to missed nursing care ( p  < .001). No significant association was found between missed nursing care and nurses' intention to leave ( p  > .05). Conclusion: The occurrence of missed nursing care was noted to be low. Implications for Nursing Management: Practical strategies such as an acuity‐based staffing system, close monitoring of rendered care and strengthening of teamwork are recommended to minimize missed nursing care.